Peningkatan Daya Saing Pelaku Umkm di Surabaya Bidang Kuliner, Kerajinan Tangan, dan Jasa Melalui Pemasaran Digital - Monica Adjeng Erwita; Yuliasti Ika Handayani; Andi Anugrah Amrullah (PeKA: Jurnal Pengabdian Kepada Masyarakat, 2021)
This community service activity is carried out as a follow-up to the Digital Marketing and Marketing Management course. There are several problems faced by partners that have been collected by students by mapping the partner's marketing strategy in the several semesters that have been undertaken. The first problem is from product management related to packaging, branding, the second problem is the limited capital for promotion, the third problem is the limited knowledge of marketing strategies and the lack of knowledge about how to make attractive promotional content through product photos and videos, the fourth problem is the ability to manage and create media social including Instagram, Facebook, website, and YouTube. Social media in the context of industrial organizations, various forms such as blogs, photo sharing, video channels and others, have become the subject of increasing interest. Therefore, from the four problems, this community service is made to help partners overcome the problems at hand. This activity is also a follow-up and application of Digital Marketing and Marketing Management courses. It is hoped that with this activity, students can apply the knowledge they have obtained to help partners improve competitiveness in terms of digital marketing.